2014
DOI: 10.1038/leu.2014.332
|View full text |Cite
|
Sign up to set email alerts
|

Comparative therapeutic value of post-remission approaches in patients with acute myeloid leukemia aged 40–60 years

Abstract: The preferred type of post-remission therapy (PRT) in patients with acute myeloid leukemia (AML) in first complete remission (CR1) is a subject of continued debate, especially in patients at higher risk of nonrelapse mortality (NRM), including patients >40 years of age. We report results of a time-dependent multivariable analysis of allogenic hematopoietic stem cell transplantation (alloHSCT) (n=337) versus chemotherapy (n=271) or autologous HSCT (autoHSCT) (n=152) in 760 patients aged 40-60 years with AML in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
99
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(106 citation statements)
references
References 59 publications
7
99
0
Order By: Relevance
“…45,46 Of particular interest are the recent results of studies evaluating RIC transplantation in middle-aged patients. [47][48][49][50] Using a time-dependent Mantel-Byar comparison in patients .45 years of age, the MRC AML15 trial showed that, compared with chemotherapy, RIC transplantation was associated with longer survival. 47 Two recent studies have even suggested that RIC might be preferred to MAC transplantation in this age range, given the lower TRM as well as better survival in some risk subgroups.…”
Section: Allogeneic Hsctmentioning
confidence: 99%
See 1 more Smart Citation
“…45,46 Of particular interest are the recent results of studies evaluating RIC transplantation in middle-aged patients. [47][48][49][50] Using a time-dependent Mantel-Byar comparison in patients .45 years of age, the MRC AML15 trial showed that, compared with chemotherapy, RIC transplantation was associated with longer survival. 47 Two recent studies have even suggested that RIC might be preferred to MAC transplantation in this age range, given the lower TRM as well as better survival in some risk subgroups.…”
Section: Allogeneic Hsctmentioning
confidence: 99%
“…47 Two recent studies have even suggested that RIC might be preferred to MAC transplantation in this age range, given the lower TRM as well as better survival in some risk subgroups. 49,50 Reliance on genetic profiles as the main treatment-stratifying tool is being increasingly challenged because of multiple recently described genetic mutations and the potential impact of mutated allele frequencies. Not all patients with ELN favorable-risk AML have a favorable outcome; for instance, should we take into account the presence of additional KIT or FLT3 poor-risk mutations in a patient with CBF-AML, or of additional ASXL1, IDH1 or DNMT3A mutations in a patient with NPM1-mutated CN-AML and no FLT3-ITD?…”
Section: Allogeneic Hsctmentioning
confidence: 99%
“…However, without subsequent treatment most patients will eventually relapse within few months. Consequently, they are offered consolidation treatment in CR1 with either conventional chemotherapy, autologous or allogeneic transplantation [2][3][4]. Among these options, high-dose chemotherapy (HDCT) with autologous stem cell transplantation (ASCT) can be applied to consolidate CR1 in AML patients who have favorable or intermediate risk cytogenetic and molecular abnormalities [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…4. Finally, The Hovon group, as already mentionned 71 recently reported results of a time-dependent multivariable analysis of allo-HSCT versus chemotherapy or ASCT in 760 patients with AML in CR1. They concluded that ASCT remains a treatment option in patients with intermediate-risk AML.…”
mentioning
confidence: 98%